Flow cytometric pitfalls in immunophenotyping of lymphomas - Ihan, Alojz (Radiology and oncology (Ljubljana), 1998)
Flow cytometry has been introduced as the most reliable method for the analysis of lymphocyte subsets. The advantage of flow cytometry is that it enables application of virtually all monoclonal antibodies (native cells), a quantitative estimation of different lymphoid cells, and that cell can be simultaneously analysed for multiple marker expression. The usage of flow cytometers requiers considerable knowledge of physics and its technical application. Moreover, several problems arise from the complexity of the biolocal systems investigated.
Keywords: Antibodies, monoclonal; Antigens, cd; diagnostika; Flow cytometry; Immunology; Immunophenotyping; limfociti; Lymphoma; metode; Pathology; pretočna citometrija